(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
The title that Silvia Casini gives to her book installs, in the paratext, one of the axes that cross from the origins of Argentine and Latin American literature. It also defines the spatial location in which the term barbarian in quotation marks will operate: Patagonia, southern Argentina (Review)